2020
DOI: 10.1002/tax.12275
|View full text |Cite
|
Sign up to set email alerts
|

Capitulum compartmentalization in Leucheria (Nassauvieae): Insights into the evolution of Asteraceae inflorescence

Abstract: An unusual feature occurs in the capitula of Leucheria (Nassauvieae, Asteraceae), some phyllaries of the involucre are twisted and/or rotated. The different spatial orientations of these phyllaries, called here paleaceous phyllaries, divide the capitulum into compartments enclosing florets and fruits. Because the internal morphology of the phyllaries could play a role in the compartmentalization, the anatomy of the phyllaries together with their different spatial arrangements was analyzed in the 49 species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This mechanism could potentially explain why among apioids pseudanthia are common in many montane or arid‐adapted species, such as representatives of the genera Tordylium , Echinophora , Dicyclophora , or Pleurospermum . Interestingly, similar secondarily compartmented or aggregated inflorescences (syncephalia) occurring in Asteraceae subtribe Nassauvinae are also considered an adaptation to dry habitats (Katinas et al, 2008; Katinas and Forte, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism could potentially explain why among apioids pseudanthia are common in many montane or arid‐adapted species, such as representatives of the genera Tordylium , Echinophora , Dicyclophora , or Pleurospermum . Interestingly, similar secondarily compartmented or aggregated inflorescences (syncephalia) occurring in Asteraceae subtribe Nassauvinae are also considered an adaptation to dry habitats (Katinas et al, 2008; Katinas and Forte, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, these features very often show variation in the same species or in the same individual. Katinas and Forte (2020) analyzed the phyllaries of the involucre in detail and concluded that most species of Leucheria have both regular capitula and capitula with paleaceous phyllaries, demonstrating that this character is too variable to be useful for classification purposes. They concluded that in the course of the tribe's evolution, Leucheria achieved what looks like a regular capitulum, but with the remnants of an ancestral secondary head evidenced in the paleaceous phyllaries and in the capitulum compartmentalization.…”
Section: Manuscript Received 19 March 2021; Acceptedmentioning
confidence: 99%
“…In the capitula with paleaceous phyllaries, the outer and inner phyllaries can bend, twist, and rotate, generating a capitulum compartmentalization where one or more florets are separated from other florets by the phyllaries (Figure 5B). The anatomy of the phyllaries was studied in detail by Katinas and Forte (2020), showing differences between the abaxial and adaxial epidermises of the phyllary, bulliform-like cells in the epidermis, and a callus at the base of the phyllary.…”
Section: Vegetative Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, Pérez2020 used the Jara2017 topology with nine terminals removed. The Jara2017 topology also was reproduced by Katinas & Forte (2020) to map evolution of inflorescence characteristics in the genus. While Lavandero2020 reported topological disagreements between their reanalyzed phylogeny and that used in Pérez2020 (including Lavandero), they did not comment (then or since) on the implications for Pérez2020's results, which would be highly sensitive to both topology and branch lengths.…”
Section: Introductionmentioning
confidence: 99%